Who Believes that the Police Use Excessive Force? Centering Racism in Research on Perceptions of the Police. (February 2023) - Drakulich, Kevin; Robles, Jesenia; Rodriguez-Whitney, Eric; Pereira, Cassidy
Objectives: Police use of excessive—even fatal—force is a significant social issue, one at the symbolic heart of the Black Lives Matter civil rights movement. However, a substantial number of Americans—disproportionately White—tend to minimize the prevalence of this issue. We seek to explain differences in these views. Methods: We look at whether experiences with the police, politics, and three measures of racial attitudes explain differences in views of the prevalence of police use of excessive force, and we specifically test for whether these factors help explain racial stratification in these views. Using data from three different recent national surveys collected by the American National Election Studies, we attempt to replicate our findings within this paper. Results: Views of police use of force are highly stratified by race and politics and racial attitudes—in particular racial resentment—play an important role in explaining these differences. Conclusions: If we hope to address this important issue, it matters that many people minimize its existence, and it matters why they minimize it. We argue that centering race in crime and justice research necessarily means centering racism.